Dampak Penyalahgunaan Kenderaan Dinas Serta Ancaman terhadap Citra dan Moralitas ASN Berdasarkan Perspektif Hukum - Hasan, Arham; Bora, Asnawati; Moonti, Roy Marthen (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This research examines the negative impact of misuse of official vehicles by State Civil Apparatus (ASN) on their image and morality, as well as the legal consequences that accompany it. The main focus of this research is to analyze how this behavior forms negative perceptions among the public and damages the integrity of ASN. The methodology used is a literature study, utilizing various sources related to law and government ethics as analysis material. The research results show that this act of abuse can weaken the level of public trust in government institutions.